The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.compchemeng.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process operating conditions on solvent thermal and oxidative degradation in post-combustion CO2 capture

Abstract: Monoethanolamine thermal and oxidative degradation Process modeling Plant design Integrated experimental and modeling study a b s t r a c tThe CO 2 post-combustion capture with amine solvents is modeled as a complex system interconnecting process energy consumption and solvent degradation and emission. Based on own experimental data, monoethanolamine degradation is included into a CO 2 capture process model. The influence of operating conditions on solvent loss is validated with pilot plant data from literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Upon an increase in MEA concentration from 25 to 40 wt.%, the reboiler duty decreased by 14%. However, the use of high concentration MEA will considerably increase the degradation rate due to a higher O 2 mass transfer at higher MEA concentrations in the absorber . Moreover, the higher solvent concentration causes an increase in viscosities and diffusion coefficient, thus increasing the operational difficulty in real practice.…”
Section: Process Improvement Of Mea‐based Co2 Capture Processmentioning
confidence: 99%
“…Upon an increase in MEA concentration from 25 to 40 wt.%, the reboiler duty decreased by 14%. However, the use of high concentration MEA will considerably increase the degradation rate due to a higher O 2 mass transfer at higher MEA concentrations in the absorber . Moreover, the higher solvent concentration causes an increase in viscosities and diffusion coefficient, thus increasing the operational difficulty in real practice.…”
Section: Process Improvement Of Mea‐based Co2 Capture Processmentioning
confidence: 99%
“…Oxidative degradation is normally proportional to the O2 content in the gas being captured [19,20]. When 30 wt% MEA is used for capture CO2 from typical FG after postcombustion, it was found that 1% O2 can result in 0.0135 kg/tCO2 MEA loss and 0.028 mol NH3 emission.…”
Section: Energy Performancementioning
confidence: 99%
“…In the 1990ies, numerous works on energy integration in the industry were realized (e.g., Maréchal et al, 1998) and from the turn of the century, different topics were studied like detailed boiler models (Dumont and Heyen, 2004) and dynamic validation (Ullrich et al, 2010). More recently, environmental issues gained in importance with research in data mining for emission control (Sainlez and Heyen, 2012) and CO 2 capture (Léonard et al, 2015). These last topics are still among the interests of CAPE research at ULg.…”
Section: Dedicated Cape Research and Teaching In The 2 Nd Cyclementioning
confidence: 99%